Sustainable Energy Technological Issues, Applications and Case Studies - Zobaa, Ahmed F.; Afifi, Sara N.; Pisica, Ioana (IntechOpen, 2016)
The sustainable energy sources are potentially employed to substitute petrol fuels in transport engines such as buses and small vehicles. Hydrogen-enriched compressed natural gas engines are forthcoming energy carriers for the internal combustion engine, with higher thermal efficiency and less pollutant emissions. The different availability of renewables has allowed various countries to adopt the most appropriate type of renewable energy technology according to their energy source adequacy/abundance. In Taiwan, ocean energy is considered as an abundant source of renewables due to its geographical location as an island. The Taiwanese government has approved the investment to construct an MW-scale demonstration electricity plant. In this book, the Taiwanese ocean energy experience is comprehensively presented. The technical and legal analyses of ocean energy implementation are provided. The challenges that they had to overcome to optimize the utilization of the most available ocean energy potential are discussed. The sustainable transition in South Africa would be a good example for implementing rooftop solar, especially in low-income communities. Apart from the environmental benefits, sustainable energy technologies can boost the socioeconomic level of developing countries. Other advantages may be the continuous supply of energy and creation of new job opportunities. Moreover, sustainable renewable energy sources such as the wind could be employed for generating electricity to operate water purification systems in remote areas. This, in turn, would overcome the health problems associated with drinking water scarcity issues. This book is an attempt to cover the sustainable energy issues from a technical perspective. Furthermore, the sustainable energy applications and existing case studies are helpful illustrations for the broad understanding of the importance of sustainable energy.